The Authority of the Indonesian Ulama Council in Certifying Halal Products From a Siyasah Syar’iyyah Perspective - Abdul Syatar; Firdayanti Firdayanti (State Institute for Islamic Studies Palu, 2022)
The emergence of public concerns regarding products that are still in doubt about the halalness of products in Indonesia makes the researcher try to understand the authority of the Indonesian Ulama Council, in this case issuing a fatwa related to the halal or haram of a product. Talking about fatwas, it cannot be separated from the authority of the Indonesian Ulama Council in issuing fatwas on the halal and haram of a product. This study employed library research with a siyasa syar'iyyah approach. The results showed that 1) the standards used by Indonesian Ulama Council in determining the halal and haram of a product by taking into account the legal status of the substances used, how to obtain them, how to produce them and how to market them, 2) related to the effectiveness of the inclusion of the halal logo and the existence of a halal certificate on every the product was still low because there were still products that did not have a halal certificate and the inclusion of a halal logo, and 3) the authority of Indonesian Ulama Council in halal certification from a siyasah syar'iyyah perspective by providing legal considerations among the people, even though it did not have binding legal force. As an implication of this study, it is hoped that there will be aware for the Muslim community to be more careful in consuming a product, especially Muslim business actors in order to understand the importance of halal certificates and the inclusion of a halal logo on each product.